Memory Buttons in Combination with Mobile Application-Induced Objective and Subjective Effects in Patients with Atopic Dermatitis. (13th February 2020) - Joergensen, Kristina M.; Vestergaard, Christian; Joergensen, Morten S.; Eiken, Aleksander; Malmstedt-Miller, Martin; Schultz, Anders N. Ø.; Deleuran, Mette; Zibert, John R.
Abstract : Background . Atopic dermatitis (AD) is a chronic skin condition where nonadherence often results in lack of disease control. Objective . We wanted to determine whether the combination of an electronic memory button and a supportive application (app) would affect the Quality of Life and subjective and objective severity measures among AD patients over one month following the patient's normal schedules of treatment. Methods . A randomized, investigator-blinded, prospective observational feasibility study for one month where patients diagnosed with AD were randomized based on POEM severity score and divided into 3 groups. The 3 groups were (1) the control group with two consultations, (2) in addition to group 1, patients also received electronic memory buttons to click every time they used their topical products, and (3) in addition to group 2, patients also received an app to track their treatment schedules. At both consultations, patients were evaluated using SCORAD, EASI, POEM, and DLQI. Results . 96 patients were enrolled and randomized, of which 83 patients completed the study. EASI and SCORAD scores were lower in all groups at 2 nd consultation (p < 0.05 ); however, these were highly significant for group 3 (p < 0.005 ), and for EASI between groups 2 and 3 (p < 0.05 ). The POEM score decreased significantly in group 3 (p = 0.024 ), and no difference was found in DLQI between visits. Conclusion . A reduction in severity following objective assessments of the AD was observed for all groups and was highly significant for patients offered a memory button and the corresponding app. Furthermore, patients reported a significant subjective beneficial effect if they used the memory button and app. This indicates that digital solutions may have a benefit in clinical practice and may reduce nonadherence and increase the wellbeing of the patients.